Multitemporal analysis of the amazon river between Corea Island (Colombia) and Aramosa Island (Brazil) (2009)
An analysis of fluvial dynamics of the Amazon River between Corea Island (Colombia) and Aramosa Island (Brazil), northwest and southeast of Leticia, respectively, was carried out for a period of 18.1 years. The analysis was made using remote sensing image processing techniques applied to images acquired at different times. LANDSAT images were compared using the Brazilian Software SPRING with the method of unsupervised classification ISOSEG, to distinguish between land and water categories. LANDSAT scenes acquired on August 4 1986, November 20 1999 and September 14 2004 were selected from a database of 44 LANDSAT images based on minimal daily water level variations, with the largest temporal variation. The multitemporal analysis revealed moderate changes in the Amazon River's morphology. Increase of lateral accretion of islands (19,19%) and recent deposition (35,80%), over the period of time analyzed (18,1 years), indicate its depositional tendency. The percent migration rate (8,61%, 0,48%/year) and the maximum migration rate (133,56 m/year) suggest the current pattern for this reach of the Amazon River is meandering. This type of analysis provides important basic information for subsequent detailed geomorphological and sedimentological studies, and is an excellent tool for understanding the dynamics of holocene Amazon fluvial systems.